Depression among college-bound students during Covid-19 attack / Normala Ismail and Mohamad Kamil Ariff Khalid - Ismail, Normala; Khalid, Mohamad Kamil Ariff (Universiti Teknologi MARA, Pahang, 2022)
Depression can be detected through students’ behaviors such as anxiety, pressure and stress. Depression among university students has been a controversial issue nowadays. The aim of this paper is to see the level of depression among college-bound students during COVID-19 attacks. The data of the study were obtained by distributing questionnaire forms to 100 female students from various faculties who are ‘trapped’ in college and unable to return home due to Movement Control Order (MCO) during COVID-19 attack. The researchers used the Beck Depression Inventory which describes the students’ level of depression and factors contributed to their depression. The data were analyzed using Statistical Package for Social Sciences (SPSS) software version 23. The result of the study showed that the students were depressed not because they cannot go home during COVID-19 attacks, but due to other factors like family, personal issues, academic performance achievement issues, communication barriers and social interaction problems related to peer relationships. It is hoped that the results of this study provide solutions to educators and students as to how depression can be overcome so that life becomes balance, safe and enjoying.